Hacking the Abismal Line: For an Artistic Decolonial Pharmacology in the Capitalocene - Baranzoni, Sara; Vignola, Paolo (Nawi, 2021)
The paper aims to analyse the social, epistemic and colonial dimension that accompanies the climate crisis and the Capitalocene, through some decolonizing artistic practices. To achieve it, we decided to adopt and use some concepts from Bernard Stiegler’s philosophy of technology, articulating them with notions, postures and perspectives of decolonial thought and in particular with Boaventura de Sousa Santos’ “epistemicide”, “abyssal line” and the “ecology of knowledges”. The artistic works by Cristian Villavicencio, Jaime Del Val and Fredy Vallejos enable this conciliation between pharmacological criticism (Stiegler) and the ecology of knowledges, embodying the function of aesthetic and socio-epistemic devices anchored to technological developments in the arts, thus capable of developing a pharmacology of the digital in a decolonial sense.
Keywords: Capitalocene, Ecology of knowledges, epistemicide, pharmacology, abismal line